CREATION OF AN INTELLIGENT SYSTEM TO SUPPORT MEDICAL DIAGNOSIS (Innovative Technologica: Methodical Research Journal, 2023)
The article deals with the issue of creating an intelligent system that works on the basis of the method of generalized assessments and helps in making medical diagnoses, based on the technology of extracting knowledge from databases. The components of the created system are described. An example of the result obtained with the help of the developed system is given.